Model Perilaku Pencarian Informasi: Analisis Teori Perilaku Pencarian Informasi Menurut Wilson - Lubis, Ryzky Amalia; Alisa, Nur; Sitompul, Surya Ningsi Wijaya; Saragih, Ahmad Tuah Wijaya; Purwaningtyas, Franindya (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
According to their own needs, various users will search for information in different ways. The pattern of a person in searching for and compiling the information he gets is called his information seeking behavior. There are at least three different perspectives on how people seek knowledge, and Wilson is responsible for all three perspectives. The user's information-seeking behavior has given rise to hypotheses that can be investigated with the help of this image. The purpose of this study is to provide an explanation of how Wilson arrived at his conclusions on the information retrieval model. What is meant by "information seeking behavior" is the act of seeking information with the intention of achieving certain goals as a direct result of pressure to achieve certain goals. In the context of this endeavor, one can only engage with basic information systems (such as newspapers, periodicals, and libraries) or computer-based information systems (Wilson, 2000). Keywords: Information Seeking Behavior, Wilson, Wilson's Behavior